DNA methylation in the APOE genomic region is associated with cognitive function in African Americans - Jiaxuan Liu; Wei Zhao; Erin B. Ware; Stephen T. Turner; Thomas H. Mosley; Jennifer A. Smith (BMC, 2018)
Abstract Background Genetic variations in apolipoprotein E (APOE) and proximal genes (PVRL2, TOMM40, and APOC1) are associated with cognitive function and dementia, particularly Alzheimer's disease. Epigenetic mechanisms such as DNA methylation play a central role in the regulation of gene expression. Recent studies have found evidence that DNA methylation may contribute to the pathogenesis of dementia, but its association with cognitive function in populations without dementia remains unclear. Methods We assessed DNA methylation levels of 48 CpG sites in the APOE genomic region in peripheral blood leukocytes collected from 289 African Americans (mean age = 67 years) from the Genetic Epidemiology Network of Arteriopathy (GENOA) study. Using linear regression, we examined the relationship between methylation in the APOE genomic region and multiple cognitive measures including learning, memory, processing speed, concentration, language and global cognitive function. Results We identified eight CpG sites in three genes (PVRL2, TOMM40, and APOE) that showed an inverse association between methylation level and delayed recall, a measure of memory, after adjusting for age and sex (False Discovery Rate q-value < 0.1). All eight CpGs are located in either CpG islands (CGIs) or CGI shelves, and six of them are in promoter regions. Education and APOE ε4 carrier status significantly modified the effect of methylation in cg08583001 (PVRL2) and cg22024783 (TOMM40), respectively. Together, methylation of the eight CpGs explained an additional 8.7% of the variance in delayed recall, after adjustment for age, sex, education, and APOE ε4 carrier status. Methylation was not significantly associated with any other cognitive measures. Conclusions Our results suggest that methylation levels at multiple CpGs in the APOE genomic region are inversely associated with delayed recall during normal cognitive aging, even after accounting for known genetic predictors for cognition. Our findings highlight the important role of epigenetic mechanisms in influencing cognitive performance, and suggest that changes in blood methylation may be an early indicator of individuals at risk for dementia as well as potential targets for intervention in asymptomatic populations.